Isometric Imbedding of Some Metric Spaces in lp-Spaces - Vestfrid, I. A (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We present a generalization of a result of Fichet, who proved in 1988 that every ulltrametric space consisting of n points is imbedded isometrically in \(l_p^{n - 1} ,p \geqslant 1\) .